(untitled) (Architecture Image Studies, 2025)
Banyuwangi is a region in Indonesia renowned for its distinctive beach tourism destinations. The beach region of Banyuwangi is susceptible to significant disaster risk. This study aimed to identify, quantify, and build a prioritization scale for disaster risk management in coastal tourism regions in Banyuwangi. The approach employed for risk identification involves data analysis and stakeholder exploration. The HVA (hazard vulnerability assessment) method was employed for risk assessment. Mitigation assessments were conducted by identifying the hazards that pose the greatest risk. The study’s findings indicate that material hazards (53%) and nature hazards (35%) pose the greatest risk. The highest risk in material hazards is exposure to marine waste and exposure to visitor/tourist waste. For nature hazards, the highest risks are tsunami (52%), extreme weather (52%), and earthquakes (50%). Mitigation was compiled by referring to the highest disaster risk by involving internal destination managers and external stakeholders, including visitors, local communities, government, and the private sector.